1964
DOI: 10.1128/jb.88.1.20-24.1964
|View full text |Cite
|
Sign up to set email alerts
|

AMINO ACID ACCUMULATION IN ETHIONINE-RESISTANT SACCHAROMYCES CEREVISIAE

Abstract: acid accumulation in ethionine-resistant Saccharomyces cerevisiae. J. Bacteriol. 88:20-24. 1964.-Recessive ethionine-resistant strains of Saccharomyces cerevisiae possess a genetic lesion affecting the concentration of amino acids nonspecifically in the expandable pool of the organism. This area, which may be linked to a methionine gene, is highly mutable and accounts for resistance to certain amino acid analogues. Other mutations result in ethionine resistance by a mechanism unrelated to the amino acid uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1965
1965
2004
2004

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Demain (1964) suggested that a site of permeation may be the point of inhibition by normal purines of a guanineless mutant of Bacillus subtilis. Permeability has also been suggested for the basis of resistance of mutants of Saccharomyces cerevisiae to ethionine (Sorsoli, Spence, and Parks, 1964). There are other mechanisms that can also explain inhibition of growth by normal purines and resistance to amino acid analogues (Fangman and Neidhardt, 1964a, b;Lewis, 1963;Martin and Moo-Penn, 1963;Moyed, 1964;Rowbury and Woods, 1961).…”
Section: Discussionmentioning
confidence: 99%
“…Demain (1964) suggested that a site of permeation may be the point of inhibition by normal purines of a guanineless mutant of Bacillus subtilis. Permeability has also been suggested for the basis of resistance of mutants of Saccharomyces cerevisiae to ethionine (Sorsoli, Spence, and Parks, 1964). There are other mechanisms that can also explain inhibition of growth by normal purines and resistance to amino acid analogues (Fangman and Neidhardt, 1964a, b;Lewis, 1963;Martin and Moo-Penn, 1963;Moyed, 1964;Rowbury and Woods, 1961).…”
Section: Discussionmentioning
confidence: 99%
“…Methionine assay. The uptake and intracellular concentration of methionine was determined by microbiological assay with Streptococcus faecalis strain 9790 as described earlier (13). The medium was assayed following removal of the cells by membrane filtration (Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic techniques. Methods leading to tetrad analysis, including mating, diploid isolation, sporulation, and genetic manipulation, were the same as those described by Sorsoli et al (5). For random analysis, the techniques above were employed except that, immediately after treatment of the sporulated diploid with snail enzyme, the ascospores were spread on the surface of TGY (1% tryptone, 2% glucose, 1% yeast extract) agar plates.…”
Section: Methodsmentioning
confidence: 99%